PERBANDINGAN RATIO DECIDENDI PUTUSAN HAKIM TERHADAP PEMBERIAN KOMPENSASI KEPADA KORBAN TINDAK PIDANA PERDANGANGAN ORANG DI INDONESIA ( TINJAUN YURIDIS PUTUSAN NOMOR: 12/PID.SUS/2021/PN KPG DAN PUTUSAN NOMOR:584 K/PID.SUS/2013/PN,SBY) - Bangkole, Lorens Soli Daud; Leo, Rudepel Petrus; Dima, Adrianus Djara (Law Faculty, Nusa Cendana University, 2023)
Human Rights (HAM) is a fundamental right of all mankind as a gift of God inherent in human beings, natural, universal, eternal associated with human dignity, equally owned by all people, regardless of gender, nationality, religion, age, language, social status, political views, etc. One of the problems related to human rights in Indonesia is the crime of trafficking in Persons which is one form recruitment, delivery, transfer, protection or acceptance of a person, by threat or use of force or any form of coercion, kidnapping, deception, lying, or other abuse of power, or vulnerable position or giving or receiving payments or obtaining benefits to obtain the consent of someone who has power over others, for the purpose of exploitation. the purpose of this article is to determine the ratio decidendi judge's decision against the provision of compensation to victims of trafficking in persons of decision number: 584/K/pid.Sus/2013/Pn Sby and to determine the recidendi ratio which is an inhibiting factor so that it does not deberikannya compensation to victims of trafficking in Persons Decision No. 12 / Pid.Sus / 2021 / PN Kpg. The results showed that: (1) based on the consideration of the Supreme Court in the decision of the trafficking in persons case above, the ratio decidendi used in providing compensation to victims of trafficking in persons in the above decision is the provision of compensation is a citizen's right, the distribution of compensation is intended as assistance or to ensure the welfare of victims of crime and as Social Security. (2) inhibiting factors so that the crime of trafficking in Persons is not given in decision Number 12/Pid.Sus / 2021 / PN Kpg namely: legal factors and the unavailability of compensation implementation guidelines.